Adapalene microemulsion for transfollicular drug delivery. Issue 8 (31st May 2013) - Bhatia, Gaurav; Zhou, Yingcong; Banga, Ajay K.
Abstract The aim of this study was to develop a microemulsion formulation of adapalene for transfollicular delivery. A pseudoternary phase diagram was developed for microemulsion consisting of oleic acid as oil phase, tween 20 as surfactant, Transcutol® as cosurfactant, and deionized water. Differential tape stripping and confocal laser scanning microscopy were performed to determine the penetration of microemulsion through hair follicles. Transmission electron microscopy, dynamic light scattering, polarizing light microscopy, and differential scanning calorimetry were performed to characterize the microstructures of microemulsion. The pH and viscosity of the microemulsions were also determined. Permeation studies were carried out in vitro on porcine ear skin over a period of 24 h using Franz diffusion cells. The drug penetration in the hair follicles increased from 0.109 ± 0.03 to 0.292 ± 0.094 μg, as the microstructure of microemulsion shifted from oil‐in‐water to bi‐continuous, with increase in water content of microemulsion. Confocal laser scanning microscopy images suggested that hair follicles provided the path for transfollicular permeation of adapalene microemulsion. These results suggest that microemulsion penetrated through hair follicles and are promising for transfollicular drug delivery. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:2622–2631, 2013